2021
DOI: 10.3390/diagnostics11050890
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Correlation of Heart Rate Variability at Diagnosis with Survival of Patients with Hepatocellular Carcinoma

Abstract: Background: Heart rate variability (HRV) indices have been shown to be associated with prognosis in various types of cancer. This study aims to assess the ability of these indices to predict survival in hepatocellular carcinoma (HCC) patients after diagnosis. Methods: We retrospectively collected data from 231 patients diagnosed with HCC between January 2014 and March 2018. The baseline clinical-pathological variables and HRV indices (extracted from Holter electrocardiogram recordings) were analyzed. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Some studies showed an association between a high HRV value and better survival rate in several cancers (e.g. breast, pancreas, prostate) ( 18 24 ). However, these studies were heterogeneous, and several had small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed an association between a high HRV value and better survival rate in several cancers (e.g. breast, pancreas, prostate) ( 18 24 ). However, these studies were heterogeneous, and several had small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The SDNN reflects the overall activity of the ANS (Vanderlei et al, 2009;Lombardi and Stein, 2011). Clinical studies have found significant associations between decreased SDNN and elevated levels of inflammatory markers, cancer progression, and reduced survival Frontiers in Physiology frontiersin.org in patients with malignant tumours (Hu et al, 2018;Ciurea et al, 2021;Wang et al, 2021;Wu et al, 2021). This study revealed that SDNN was independently associated with overall survival in ES-SCLC patients, suggesting that SDNN has the potential to serve as a prognostic factor in ES-SCLC patients.…”
Section: Discussionmentioning
confidence: 68%
“…HRV is the variation in duration of successive R-R intervals, and it reflects ANS regulation (Camm et al, 1996;Lombardi and Stein, 2011). Most previous studies have shown that HRV has predictive value in the overall survival of cancer patients; that is, ANS dysfunction (characterized by decreased HRV parameters) may predict shorter survival of cancer patients (Ciurea et al, 2021;Wang et al, 2021;Wu et al, 2022). For example, the HRV parameter "standard deviation of the normal-normal intervals" (SDNN) is independently correlated with overall survival in patients with hepatocellular carcinoma (Ciurea et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the sympathetic nervous system is involved in many types of cancer [ 21 , 36 , 37 , 38 , 39 ]. This subdivision of the nervous system acts through noradrenaline, which is released by the local sympathetic fibers in the vicinity of or even inside the gastric tumors and through epinephrine released from the adrenal gland [ 21 ].…”
Section: Discussionmentioning
confidence: 99%